Antibacterial Activity of Lactic Acid Bacteria Isolated from Fermented Ethiopian Traditional Dairy Products against Food Spoilage and Pathogenic Bacterial Strains - Abayeneh Girma; Aleka Aemiro (Journal of Food Quality)
Fermented Ethiopian traditional dairy products containing LAB that show antibacterial activities against various food spoilage and pathogenic bacteria have been used for the preservation of fermented dairy products for a long time. However, there are no comprehensive scientific reports on the antibacterial activity of LAB isolated from various fermented dairy products in Pawe Woreda. The objective of the study was to evaluate the antibacterial activity of LAB isolated from traditionally fermented Ethiopian dairy products against spoilage and pathogenic bacteria. Thirty-five samples of fermented dairy products were collected from three cattle-farming areas of Pawe Woreda. A total of 97 LAB were isolated and screened primarily using the perpendicular streak plate method against 3 Gram-positive and 3 Gram-negative bacterial strains. Out of the 97 strains, 10 were active against at least two of the tested bacteria, of which 7 strains were selected for secondary screening by their broad-spectrum antibacterial activities. The seven in vitro antibacterial activities of the extract ranged from 5 to 16 mm in diameter during the secondary screening. In this study, Z2, Z4, and N2 strains exhibited the highest inhibition zone with broad-spectrum activity against all tested bacteria. The MIC and MBC values range from 0.10 to 0.30 µg/µL and 0.20 to 0.50 µg/µL, respectively. Following morphological, physiological, biochemical, and molecular characteristics, seven potent strains were identified as Lactobacillus acidophilus, Lactobacillus paracasei, Lactobacillus plantarum, Lactobacillus rhamnosus, Leuconostoc mesenteroides, Streptococcus thermophilus, and Lactococcus lactis. According to the findings of this study, Ethiopian fermented dairy products were the most potent source of bioactive compounds with potential effects against food spoilage and pathogenic bacterial strains.